Platform for change : a message from Stafford Beer - Beer, Stafford (London ; New York : Wiley, 1975)
A new sort of book for a new sort of world.
Includes bibliographical references.
ucj 17/01/2019
Loans
Keywords: System theory; Cybernetics; Operations research